Preparation method of photo-thermal biomass cellulose hydrogel

By mixing natural porous cellulose with other chemical substances and preparing it for freeze, 3DJanus photothermal natural biomass cellulose hydrogel was obtained, solving the problem of insufficient performance of photothermal materials in the prior art, and achieving efficient interfacial evaporation and water resource treatment.

CN119570064APending Publication Date: 2025-03-07XINJIANG UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411467167.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the prior art, it is difficult to find a high-quality photothermal material with simple preparation, natural green and strong photothermal conversion performance in the interface evaporation system to effectively evaporate moisture.

Method used

Using natural porous cellulose as raw material, it is mixed with sodium hydroxide, crosslinking agent, photothermal conversion material and network construction material to produce 3DJanus photothermal natural biomass cellulose hydrogel and prepared by freezing.

Benefits of technology

It realizes efficient interfacial evaporation, with the interface evaporation rate reaching 3.71 kg·m-2·h-1, and the material preparation is simple and low-cost, and it is suitable for seawater desalination and wastewater purification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119570064A_ABST
    Figure CN119570064A_ABST
Patent Text Reader

Abstract

The invention discloses a photo-thermal biomass cellulose hydrogel preparation method, which sequentially comprises: S1, uniformly mixing natural biomass cellulose, sodium hydroxide, a cross-linking agent, a photo-thermal conversion material and a network construction material to obtain a JanusA material, adding the JanusA material into a hydrophobic material, and uniformly mixing to obtain a JanusB material; and step S2, freezing the Janus B material prepared in the step S1, so as to obtain the Janus photo-thermal natural biomass cellulose hydrogel. The 3DJanus natural biomass cellulose hydrogel disclosed by the invention has excellent photo-thermal performance: the temperature can be quickly raised under the irradiation of sunlight, and water is converted into water vapor, so that efficient interface evaporation is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional materials, and in particular to a method for preparing a photothermal biomass cellulose hydrogel. Background Art

[0002] With the rapid growth of the world's population and the development of science and technology, water consumption has continued to increase, and water has become an indispensable part of people's lives and industries. However, the increase in water pollution and the long-standing problem of improper water resource management have led to a gradual increase in pollutant-related diseases, which have begun to threaten human health and survival. In recent decades, these have become major issues of global concern. Therefore, it is very necessary to recognize the importance of water resources and ensure that they are protected by developing new technologies.

[0003] Solar energy is an inexhaustible green energy source that has been successfully applied in various fields and has also opened the door to solar-driven interfacial evaporation technology. It is worth noting that photothermal conversion materials are crucial in absorbing light energy and converting it into heat energy, which is of great help in the effective evaporation of water. Therefore, it is crucial to select and use high-quality photothermal conversion materials in interfacial evaporation systems.

[0004] The application of interfacial evaporation technology has been developed into many fields, such as hydropower co-production, sterilization, sewage treatment, etc. The development of interfacial evaporation technology has brought new water purification technology and brought great benefits to society. Therefore, it is necessary to design an interfacial evaporation material that is simple to prepare, natural and green, and has strong photothermal conversion performance. Summary of the invention

[0005] The present invention provides a 3D Janus photothermal natural biomass cellulose hydrogel for solar interface evaporation and a preparation method thereof. The method uses natural porous cellulose as a raw material, and uniformly mixes sodium hydroxide, a cross-linking agent, a photothermal conversion material, and a network construction material to generate a hydrogel to impart photothermal properties, and then obtains the photothermal natural biomass cellulose hydrogel by freezing. The preparation method of the present invention has a simple process and is easy to scale up. The obtained natural biomass cellulose hydrogel has excellent photothermal properties and has good application prospects in the fields of solar energy utilization, seawater desalination, etc.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a photothermal biomass cellulose hydrogel comprises the following steps in sequence: Step S1, mixing natural biomass cellulose (CNF), sodium hydroxide, a cross-linking agent, a photothermal conversion material, and a network construction material to obtain a JanusA material, and adding the above-mentioned JanusA material to a hydrophobic material and mixing them to obtain a JanusB material; Step S2, freezing the Janus B material obtained in step S1 to obtain Janus photothermal natural biomass cellulose hydrogel.

[0007] As one embodiment of the present invention, the natural porous cellulose natural biomass cellulose material is at least one of cotton fiber, hemp fiber, straw, bamboo fiber, etc. Preferably, it is cotton fiber or hemp fiber. More preferably, it is cotton fiber.

[0008] As one embodiment of the present invention, the cross-linking agent is at least one of citric acid, genipin, tannic acid, epigallocatechin gallate, and vanillin, and more preferably citric acid.

[0009] As one embodiment of the present invention, the photothermal conversion material is at least one of carbon black, graphene oxide, carbon graphene, carbon fiber, carbon biomass fiber, carbon biomass tube, graphite, coal, artificial graphite, expanded graphite, activated carbon, amorphous carbon, carbon ash, natural biomass cellulose carbon, charcoal, etc. Preferably, it is carbon black, graphene oxide, carbon graphene. More preferably, it is carbon black.

[0010] As one embodiment of the present invention, the network building material is at least one of aluminum phosphate (AP), aluminum sulfate, aluminum tripolyphosphate, aluminum dihydrogen phosphate, aluminum chloride, aluminum nitrate, etc. Preferably, it is aluminum phosphate, aluminum sulfate, aluminum tripolyphosphate, and more preferably aluminum phosphate.

[0011] As one embodiment of the present invention, the hydrophobic material is at least one of polydimethylsiloxane (PDMS), polytetrafluoroethylene (PTFE), fluorinated polyethylene, etc. Preferably, it is PDMS.

[0012] As one embodiment of the present invention, the concentration of the sodium hydroxide is 0.5-50 mol / L. Preferably, the concentration of the sodium hydroxide is 1 mol / L.

[0013] As one embodiment of the present invention, the concentration of the cross-linking agent is 1-200 mol / L. Preferably, the concentration of the cross-linking agent is 1 mol / L.

[0014] As one embodiment of the present invention, the mass ratio of the natural biomass cellulose to the cross-linking agent is 1:0.1 to 3. Preferably, the mass ratio of the natural biomass cellulose to the cross-linking agent is 4:5.

[0015] As one embodiment of the present invention, the mass ratio of the sodium hydroxide solution to the photothermal conversion material is 1000:1 to 500. Preferably, the mass ratio of the sodium hydroxide solution to the photothermal conversion material is 20:1.

[0016] As one embodiment of the present invention, the mass ratio of the natural biomass cellulose to the network building material is 1000:1 to 100. Preferably, the mass ratio of the natural biomass cellulose to the network building material is 80:1.

[0017] As one embodiment of the present invention, the mass ratio of the natural biomass cellulose to the hydrophobic material is 1000:1 to 200. Preferably, the mass ratio of the natural biomass cellulose to the hydrophobic material is 89:10.

[0018] As one embodiment of the present invention, the reaction conditions in step S1 are: temperature of 15° C. to 35° C., and time of 2 h to 8 h.

[0019] As one of the embodiments of the present invention, the cleaning in step S1 includes alcohol washing and water washing, the alcohol washing uses 95% ethanol or anhydrous ethanol, and the water washing uses deionized water.

[0020] As one of the embodiments of the present invention, the freezing method in step S2 is refrigerator freezing or liquid nitrogen freezing.

[0021] As one embodiment of the present invention, the freezing temperature in step S2 is -196°C to 0°C, and the freezing time is 2 to 180 minutes.

[0022] The second object of the present invention is to provide a solar interfacial evaporation 3D Janus photothermal natural biomass cellulose hydrogel prepared by the aforementioned method.

[0023] The third object of the present invention is to provide the application of the aforementioned solar interface evaporation 3D Janus natural biomass cellulose photothermal water gel in water evaporation, seawater desalination, and wastewater purification.

[0024] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of the present invention is simple in process, easy to operate, and low in cost, and can be used for large-scale batch production.

[0025] (2) The 3D Janus natural biomass cellulose hydrogel of the present invention has excellent photothermal properties: it can quickly heat up under sunlight and convert water into water vapor, achieving efficient interfacial evaporation, and its interfacial evaporation rate can reach 3.71 kg·m -2 ·h -1 .

[0026] (3) The 3D Janus natural biomass cellulose hydrogel of the present invention can be used as a high-quality and efficient photothermal interface evaporation material for seawater desalination and wastewater purification.

[0027] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. The specific implementation of the present invention is given in detail by the following embodiments and their accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of this application. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 This is a SEM photo of the morphology test of the natural biomass cellulose hydrogel product prepared in Example 1.

[0029] Figure 2 The hydrogel products prepared in Example 1, Comparative Example 1 and Comparative Example 2 were exposed to sunlight (1000 W·m -2 ) Comparison of the temperature rise of the surface under illumination.

[0030] Figure 3 The hydrogel products prepared in Example 1, Comparative Example 1 and Comparative Example 2 were exposed to sunlight (1000 W·m -2 ) Comparison of water evaporation rates in beakers under illumination.

[0031] Figure 4 The hydrogel products prepared in Example 1, Comparative Example 1 and Comparative Example 2 were exposed to sunlight (1000 W·m -2 ) Comparison of the temperature increase on the sample surface in the beaker under irradiation.

[0032] Figure 5 This is a schematic diagram for comparing the absorbance of simulated reactive brilliant red printing and dyeing wastewater before and after purification.

[0033] Figure 6 This is a schematic diagram of the comparison of ion concentrations before and after the purification of reactive brilliant red dyeing wastewater.

[0034] Figure 7 Schematic diagram of the preparation steps proposed in the present invention. DETAILED DESCRIPTION

[0035] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention. The present invention is described in more detail by way of example with reference to the accompanying drawings in the following paragraphs. It should be noted that the accompanying drawings are all in a very simplified form and are not in precise proportions, and are only used to facilitate and clearly assist in explaining the purpose of the embodiments of the present invention.

[0036] Test method: 1. Morphology test: The morphology of natural biomass cellulose hydrogel samples was characterized by scanning electron microscopy (SEM HITACHI-SU8010 Co., Ltd., Japan).

[0037] 2. Photothermal heating performance test: The surface temperature changes of the hydrogel samples under lighting conditions were recorded using a thermal imager (UV-Vis-NIR LAMBDA950, PerkinElmer GmbH).

[0038] 3. Water evaporation test: The hydrogel was placed in a beaker containing a large amount of water and irradiated with a xenon lamp (CEL-PE300L-3A) equipped with an AM 1.5 filter to simulate sunlight. At the same time, a solar meter (CEL-FZ-A) was used to calibrate the sunlight intensity to maintain it at one sun (1000 W·m -2 ), an electronic balance records the mass loss of water in the beaker to measure the interfacial evaporation capacity of the hydrogel sample, and a thermal imager (Uti320E) records the surface temperature change of the hydrogel sample in the beaker.

[0039] Example 1 A method for preparing 3D Janus photothermal natural biomass cellulose hydrogel for solar interfacial evaporation comprises the following steps: Dissolve 0.1g carbon black in 2ml 1mol / L NaOH solution, add 0.1ml AP, and disperse evenly with an ultrasonic grinder. Add 8ml CNF, stir at room temperature for 6h, and then let the mixed sol stand at room temperature for 24h.

[0040] Pour the mixed sol after the reaction in step S1 into the lotus mold and freeze it in a refrigerator for 12 hours. Then add CA aqueous solution (10 ml, 1 mol / L) to the frozen sol, refrigerate the mixture in a refrigerator for 12 hours, and wash the obtained hydrogel repeatedly with deionized water. Freeze it in the refrigerator for 24 hours. After the freezing is completed, Janus natural biomass cellulose hydrogel (lotus hydrogel) is obtained.

[0041] Example 2 A method for preparing a photothermal natural biomass cellulose hydrogel for solar interfacial evaporation comprises the following steps: (1) Dissolve 0.1 g of carbon black in 2 ml of 1 mol / L NaOH solution, add 0.1 ml of AP, and disperse evenly using an ultrasonic grinder. Add 8 ml of CNF, stir at room temperature for 6 h, and then let the mixed sol stand at room temperature for 24 h.

[0042] (2) Pour the mixed sol after the reaction in step S1 into a plastic cup and freeze it in a refrigerator for 12 hours. Then add CA aqueous solution (10 ml, 1 mol / L) to the frozen sol, refrigerate the mixture in a refrigerator for 12 hours, and wash the obtained hydrogel repeatedly with deionized water. Freeze it in a refrigerator for 24 hours. After freezing, Janus natural biomass cellulose hydrogel (1wt% hydrogel) is obtained.

[0043] Comparative Example 1 The natural biomass cellulose was placed in a refrigerator and frozen for 24 hours. After the freezing, the original natural biomass cellulose hydrogel (original hydrogel) was obtained.

[0044] Comparative Example 2 A method for preparing a photothermal natural biomass cellulose hydrogel for solar interfacial evaporation comprises the following steps: (1) Dissolve 0.05 g of carbon black in 2 ml of 1 mol / L NaOH solution, add 0.1 ml of AP, and disperse evenly using an ultrasonic grinder. Add 8 ml of CNF, stir at room temperature for 6 h, and then let the mixed sol stand at room temperature for 24 h.

[0045] (2) Pour the mixed sol after the reaction in step S1 into a plastic cup and freeze it in a refrigerator for 12 hours. Then add CA aqueous solution (10 ml, 1 mol / L) to the frozen sol, refrigerate the mixture in a refrigerator for 12 hours, and wash the obtained hydrogel repeatedly with deionized water. Freeze it in a refrigerator for 24 hours. After freezing, Janus natural biomass cellulose hydrogel (0.5wt% hydrogel) is obtained.

[0046] Comparative Example 3 A method for preparing a photothermal natural biomass cellulose hydrogel for solar interfacial evaporation comprises the following steps: (1) Dissolve 0.15 g of carbon black in 2 ml of 1 mol / L NaOH solution, add 0.1 ml of AP, and disperse evenly using an ultrasonic grinder. Add 8 ml of CNF, stir at room temperature for 6 h, and then let the mixed sol stand at room temperature for 24 h.

[0047] (2) Pour the mixed sol after the reaction in step S1 into a plastic cup and freeze it in a refrigerator for 12 hours. Then add CA aqueous solution (10 ml, 1 mol / L) to the frozen sol, refrigerate the mixture in a refrigerator for 12 hours, and wash the obtained hydrogel repeatedly with deionized water. Freeze it in a refrigerator for 24 hours. After freezing, Janus natural biomass cellulose hydrogel (1.5wt% hydrogel) is obtained.

[0048] Comparative Example 4 A method for preparing a photothermal natural biomass cellulose hydrogel for solar interfacial evaporation comprises the following steps: (1) Dissolve 0.2 g of carbon black in 2 ml of 1 mol / L NaOH solution, add 0.1 ml of AP, and disperse evenly using an ultrasonic grinder. Add 8 ml of CNF, stir at room temperature for 6 h, and then let the mixed sol stand at room temperature for 24 h.

[0049] (2) Pour the mixed sol after the reaction in step S1 into a plastic cup and freeze it in a refrigerator for 12 hours. Then add CA aqueous solution (10 ml, 1 mol / L) to the frozen sol, refrigerate the mixture in a refrigerator for 12 hours, and wash the obtained hydrogel repeatedly with deionized water. Freeze it in a refrigerator for 24 hours. After freezing, Janus natural biomass cellulose hydrogel (2wt% hydrogel) is obtained.

[0050] 1. Morphology comparison The morphology of the natural biomass cellulose hydrogel products prepared in Example 1 was tested respectively, and the results were as follows: Figure 3 As shown, Figure 1 This is the 3D Janus natural biomass cellulose hydrogel (lotus hydrogel) of Example 1.

[0051] Figure 1 The scanning electron microscope image shows that the lotus natural biomass cellulose hydrogel prepared by freezing presents a unique sponge-like porous morphology. The lotus natural biomass cellulose hydrogel is a porous structure composed of hundreds of fiber sheets / tubes with 3D interconnected pores of about 20-60 μm. Figure 1 It can be seen that the photothermal natural biomass cellulose hydrogel containing carbon black, sodium hydroxide, citric acid, and AP has a large number of biomass particles on the surface while maintaining its original structure, proving the successful compounding of biomass particles (photothermal materials). From the perspective of solar interfacial evaporation, this sponge-like bioporous material has many large pores of different sizes, which can promote the rapid transport of water molecules to evaporate water.

[0052] 2. Comparison of Photothermal Heating Performance Test The products obtained in Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were tested for their photothermal heating performance. -2 ) under the irradiation of sunlight, the surface temperature of different samples changes with the solar irradiation time as shown in the following figure. Figure 4 shown.

[0053] from Figure 2It can be seen that the surface temperature of 0.5wt% hydrogel, 1wt% hydrogel, 1.5wt% hydrogel and 2wt% hydrogel gradually increased within tens of seconds, while the temperature of the original hydrogel hardly changed. After irradiation for 120 s, the 2wt% hydrogel obtained a higher and uniform surface temperature (72 ℃). At the same time, as the sunlight was turned off, the surface temperature of the photothermal hydrogel changed dynamically, and the sample gradually returned to room temperature, showing good photothermal response performance. The photothermal natural biomass cellulose hydrogel containing carbon black has a faster heating rate than the original natural biomass cellulose hydrogel, and the surface temperature reached under illumination is higher than that of the original natural biomass cellulose hydrogel, proving that carbon black is a very excellent photothermal material that can improve the photothermal heating performance.

[0054] 3. Comparison of water evaporation test The hydrogel products prepared in Example 1, Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were subjected to water evaporation tests. The results of the changes in the mass of water in the beakers of different samples with the solar irradiation time under one sunlight are as follows: Figure 3 shown.

[0055] like Figure 3 As shown in the figure, under the condition of sunlight irradiation, the water mass in the beaker changes with the increase of irradiation time. Among them, the water evaporation rate of lotus hydrogel can reach 3.71kg·m -2 ·h -1 , respectively, the original hydrogel (0.93 kg·m -2 ·h -1 ), 0.5wt% hydrogel (1.74kg·m -2 ·h -1 ), 1wt% hydrogel (2.28kg·m -2 ·h -1 ), 1.5wt% hydrogel (1.96kg·m -2 ·h -1 ) and 2wt% hydrogel (1.77 kg·m -2 ·h -1 ). The results show that the 3D Janus photothermal natural biomass cellulose hydrogel of the present invention has excellent water evaporation effect.

[0056] 4. Comparison of water evaporation temperature rise test The products obtained in Example 2, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were respectively tested for their photothermal heating performance in a water evaporation test. The surface temperature changes of different samples in a beaker containing aqueous solution under the irradiation of one sun are shown in the following table: Figure 4 shown.

[0057] The study found that even when sunlight was irradiated on the surface of the natural biomass cellulose hydrogel floating in the aqueous solution, the surface temperature of the product prepared in Example 2 would be significantly different.

[0058] from Figure 4 It can be seen that when the 1wt% hydrogel is placed in an aqueous solution and treated under one sun for 60 min, its surface temperature can reach about 41.9°C, which is much higher than the surface temperature of the original hydrogel (26.7°C). This shows that when the photothermal natural biomass cellulose hydrogel (1wt% hydrogel) is used in water evaporation experiments, its excellent photothermal effect can be used to heat water to generate steam.

[0059] Comparison of printing and dyeing wastewater purification experiments Figure 5 and Figure 6 To simulate the absorbance comparison and ion concentration comparison of reactive brilliant red printing and dyeing wastewater before and after purification, as shown in the figure, after using hydrogel to purify the simulated printing and dyeing wastewater, its absorbance and ion concentration decreased significantly, proving that the hydrogel designed in this project can effectively solve the problem of printing and dyeing wastewater treatment.

[0060] Example 3 Effects of different natural biomass cellulose materials on photothermal performance Referring to Example 1, the only difference is that the cotton fiber is adjusted to hemp fiber, and a different photothermal biomass hydrogel (referred to as hemp fiber natural biomass cellulose hydrogel) is prepared.

[0061] Referring to Example 1, the only difference is that the cotton fiber is changed to bamboo fiber, and a different photothermal biomass hydrogel (referred to as bamboo fiber natural biomass cellulose hydrogel) is prepared.

[0062] Referring to Example 1, the only difference is that the cotton fiber is changed to straw, and different photothermal biomass hydrogels (referred to as straw natural biomass cellulose hydrogels) are prepared.

[0063] The photothermal heating performance of the photothermal biomass hydrogels of the aforementioned different natural biomass cellulose materials in Example 1 and Example 3 was tested. Under sunlight irradiation, the surface temperatures of different samples after irradiation for 120 s are shown in Table 1.

[0064] Table 1 Photothermal heating performance test of photothermal natural biomass cellulose hydrogel prepared in Example 1 and Example 3 sample Surface temperature (℃) 3DJanus natural biomass cellulose hydrogel 72.0 Hemp fiber natural biomass cellulose hydrogel 68.2 Bamboo fiber natural biomass cellulose hydrogel 67.9 Straw natural biomass cellulose hydrogel 70.1 As can be seen from Table 1, after being irradiated with sunlight, the photothermal water gels made from different natural biomass cellulose materials all have certain photothermal effects, and the surface temperature can continue to rise within 120 s. The photothermal biomass hydrogel (3DJanus natural biomass fiber hydrogel) can be heated to 72.0 ℃, while under the same conditions, the hemp fiber natural biomass cellulose hydrogel, hemp fiber natural biomass cellulose hydrogel, and hemp fiber natural biomass cellulose hydrogel can be heated to 68.2 ℃, 67.9 ℃, and 70.1 ℃, respectively. It is proved that the photothermal biomass cellulose hydrogel made from natural biomass cellulose materials (such as cotton fiber, hemp fiber, bamboo fiber and straw) can achieve different photothermal heating effects by changing the biomass cellulose material. Among them, cotton fiber natural biomass cellulose hydrogel is preferred.

[0065] Example 4 Effects of different preparation methods on photothermal performance Referring to Example 1, the only difference was that the reaction time was adjusted to 1 h, and a different natural biomass cellulose hydrogel (denoted as natural biomass cellulose hydrogel #1) was prepared.

[0066] Referring to Example 1, the only difference was that the reaction time was adjusted to 2 h, and a different natural biomass cellulose hydrogel (denoted as natural biomass cellulose hydrogel #2) was prepared.

[0067] Referring to Example 1, the only difference was that the reaction time was adjusted to 3 h, and a different natural biomass cellulose hydrogel (denoted as natural biomass cellulose hydrogel #3) was prepared.

[0068] Referring to Example 1, the only difference was that the reaction time was adjusted to 4 h, and a different natural biomass cellulose hydrogel (denoted as natural biomass cellulose hydrogel #4) was prepared.

[0069] Referring to Example 1, the only difference was that the reaction time was adjusted to 5 h, and a different natural biomass cellulose hydrogel (denoted as natural biomass cellulose hydrogel #5) was prepared.

[0070] The photothermal heating performance test was carried out on the preparation methods of the above-mentioned different natural biomass cellulose materials in Example 1 and Example 4. Under sunlight irradiation, the surface temperatures of different samples after irradiation for 120 s are shown in Table 2.

[0071] Table 2 Photothermal heating performance test of photothermal natural biomass cellulose hydrogels prepared in Example 1 and Example 4 sample Surface temperature (℃) 3DJanus natural biomass cellulose hydrogel 72.0 Natural biomass cellulose hydrogel #1 60.9 Natural biomass cellulose hydrogel #2 61.8 Natural biomass cellulose hydrogel #3 62.0 Natural biomass cellulose hydrogel #4 65.9 Natural biomass cellulose hydrogel #5 69.2 It can be seen from Table 2 that after being irradiated with sunlight, the natural biomass cellulose hydrogel (Example 1) and other hydrogels have a certain photothermal effect, and the surface temperature can continue to rise within 120 s. The 3DJanus natural biomass cellulose hydrogel can be heated to 72 °C, while under the same conditions, the maximum temperature of other natural biomass cellulose hydrogels is lower than 70 °C, proving that the reaction time has a significant effect on the photothermal performance of the hydrogel.

[0072] Implementation 4 Effects of different photothermal conversion materials on photothermal performance Referring to Example 1, the only difference is that the carbon black is adjusted to graphene oxide, and different natural biomass cellulose hydrogels (referred to as graphene oxide biomass cellulose hydrogels) are prepared.

[0073] Referring to Example 1, the only difference is that the carbon black is adjusted to carbon graphene, and a different natural biomass cellulose hydrogel (referred to as carbon graphene biomass cellulose hydrogel) is prepared.

[0074] Referring to Example 1, the only difference is that the carbon black is adjusted to carbon biomass tubes, and different natural biomass cellulose hydrogels (referred to as carbon biomass tube biomass cellulose hydrogels) are prepared.

[0075] Referring to Example 1, the only difference is that the carbon black is adjusted to graphite, and different natural biomass cellulose hydrogels (referred to as graphite biomass cellulose hydrogels) are prepared.

[0076] The photothermal heating performance test was carried out on the preparation methods of the above-mentioned different natural biomass cellulose materials in Example 1 and Example 5. Under the irradiation of sunlight, the surface temperatures of different samples after irradiation for 120 s are shown in Table 3.

[0077] Table 3 Photothermal heating performance test of photothermal natural biomass cellulose hydrogels prepared in Example 1 and Example 5 sample Surface temperature (℃) 3DJanus natural biomass cellulose hydrogel 72.0 Graphene oxide biomass cellulose hydrogel 59.3 Carbon graphene biomass cellulose hydrogel 60.9 Carbon biomass tubes Biomass cellulose hydrogel 63.2 Graphite biomass cellulose hydrogel 64.5 It can be seen from Table 3 that after being irradiated with sunlight, the natural biomass cellulose hydrogel (Example 1) and other hydrogels have a certain photothermal effect, and the surface temperature can continue to rise within 120 s. The 3DJanus natural biomass cellulose hydrogel can be heated to 72 °C, while the maximum temperature of other natural biomass cellulose hydrogels is lower than 65 °C under the same conditions, which proves that the photothermal conversion material has a significant effect on the photothermal performance of the hydrogel.

[0078] In summary, the 3D Janus natural biomass cellulose hydrogel for solar interface evaporation and its preparation method provided by the present invention have the characteristics of simple preparation, low cost, and easy large-scale production. It also has excellent photothermal performance: the surface temperature can rise rapidly under sunlight, and can be used as an efficient solar interface evaporation material for seawater desalination and wastewater purification.

[0079] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a photothermal biomass cellulose hydrogel, characterized in that: The steps are as follows: Step S1, mixing natural biomass cellulose, sodium hydroxide, a cross-linking agent, a photothermal conversion material, and a network construction material to obtain a JanusA material, and adding the JanusA material to a hydrophobic material and mixing them to obtain a JanusB material; Step S2, freezing the Janus B material obtained in step S1 to obtain Janus photothermal natural biomass cellulose hydrogel.

2. The method for preparing a photothermal biomass cellulose hydrogel according to claim 1, characterized in that: The natural biomass cellulose material is at least one of cotton fiber, hemp fiber, straw, bamboo fiber and the like.

3. The method for preparing a photothermal biomass cellulose hydrogel according to claim 1, characterized in that: The cross-linking agent is at least one of citric acid, genipin, tannic acid, epigallocatechin gallate and vanillin.

4. The method for preparing a photothermal biomass cellulose hydrogel according to claim 1, characterized in that: The photothermal conversion material is at least one of carbon black, graphene oxide, carbon graphene, carbon fiber, carbon biomass fiber, carbon biomass tube, graphite, coal, artificial graphite, expanded graphite, activated carbon, amorphous carbon, carbon ash, natural biomass cellulose carbon, charcoal, etc.

5. The method for preparing a photothermal biomass cellulose hydrogel according to claim 1, characterized in that: The network building material is at least one of aluminum phosphate, aluminum sulfate, aluminum tripolyphosphate, aluminum dihydrogen phosphate, aluminum chloride, aluminum nitrate, and the like.

6. The method for preparing a photothermal biomass cellulose hydrogel according to claim 1, characterized in that: The hydrophobic material is at least one of polydimethylsiloxane, polytetrafluoroethylene, fluorinated polyethylene and the like.

7. The method for preparing a photothermal biomass cellulose hydrogel according to claim 1, characterized in that: In step S1, the concentration of the sodium hydroxide is 0.5-50 mol / L; the concentration of the cross-linking agent is 1-200 mol / L; The mass ratio of the natural biomass cellulose to the cross-linking agent is 1:0.1-3; The mass ratio of the sodium hydroxide solution to the photothermal conversion material is 1000:1-500; The mass ratio of natural biomass cellulose to network building material is 1000:1-100; The mass ratio of natural biomass cellulose to the hydrophobic material is 1000:1-200.

8. The method for preparing a photothermal biomass cellulose hydrogel according to claim 1, characterized in that: The preparation reaction conditions of the JanusA material in step S1 are: temperature of 15°C to 35°C and time of 2h to 8h.

9. The method for preparing a photothermal biomass cellulose hydrogel according to claim 1, characterized in that: The freezing temperature in step S2 is -196°C to 0°C, and the freezing time is 2 to 180 minutes.

10. The method for preparing a photothermal biomass cellulose hydrogel according to claim 1, characterized in that: The prepared Janus photothermal natural biomass cellulose hydrogel is used in solar interfacial evaporation, seawater desalination, and wastewater purification.

Citation Information

Cited By

  • Walnut shell photo-thermal conversion method based on molecular sieve coupling nanometer zero-valent iron

    CN120155442A